1996
DOI: 10.1016/0014-5793(96)00212-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of ETB receptors in normotensive and hypertensive rats as revealed by the non‐peptide selective ETB receptor antagonist Ro 46‐8443

Abstract: We used Ro 46-8443, non-peptidic antagonist selective of endothelin ETB receptors, to study the role of ET8 receptors in rat hypertension models. In normotensive rats, Ro 46-8443 decreased blood pressure, but in SHR and DOCA rats, it induced a pressor effect, due to blockade of ETs-mediated release of nitric oxide since L-NAME prevented it. In rats rendered hypertensive by chronic L-NAME, Ro 46-8443 did not induce a pressor but depressor effect. Thus, in DOCA rats and SHR, Ro 46-8443 reveals a predominant infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 18 publications
3
21
0
Order By: Relevance
“…Blockade of the ET B receptor resulted in further increase in blood pressure in hypertensive animals. This finding is in line with previous findings (5,15,23,30) and supports a protective role for ET-1 signaling through the ET B receptor in this model of hypertension. The pressor effect of A-192621 may occur as a result of the inhibition of nitric oxide release mediated by the ET B receptor.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Blockade of the ET B receptor resulted in further increase in blood pressure in hypertensive animals. This finding is in line with previous findings (5,15,23,30) and supports a protective role for ET-1 signaling through the ET B receptor in this model of hypertension. The pressor effect of A-192621 may occur as a result of the inhibition of nitric oxide release mediated by the ET B receptor.…”
Section: Discussionsupporting
confidence: 93%
“…This assumption is based on previous findings using the same experimental model in which the pressor effect of another selective ET B antagonist (Ro46-8443) was abolished by pretreatment with N -nitro-L-arginine methyl ester (5). The activation of the ET A receptors by increased ET-1 could also contribute to the elevation of blood pressure after the administration of a selective ET B antagonist although the pressor effect of the selective ETB antagonist Ro 46-8443 was reported to be unaffected by the administration of a selective ETA antagonist (5). A more recent study however, showed that the administration of ABT-627 (ET A selective antagonist) decreased mean arterial pressure in rats in a high-salt diet treated with the ET B antagonist A-192621 (31).…”
Section: Discussionmentioning
confidence: 99%
“…29 Similar findings were observed using Ro 46 -8443, the nonpeptide selective ET B receptor antagonist. 31 In separate experiments, intravenous administration of A-192621 (3 mg/kg) to DOCA-salt hypertensive rats produced increases of 10 to 15 mm Hg in BP and decreases of about 60% in renal blood flow, changes that were greater than those observed in uninephrectomized control normotensive animals (increases of 5 to 10 mm Hg in BP and decreases of about 40% in renal blood flow) (Y.M. et al, unpublished data, 1998).…”
Section: Matsumura Et Al February 1999 763mentioning
confidence: 99%
“…Overall, its non-peptidic nature, potency and ETB receptor selectivity make Ro 46-8443 a unique tool which may make it possible to explore the role of ETB receptors in different animal models such as hypertension [32].…”
Section: Discussionmentioning
confidence: 99%